2000
DOI: 10.1136/heart.84.4.425
|View full text |Cite
|
Sign up to set email alerts
|

A multifilamented electrode in the middle cardiac vein reduces energy requirements for defibrillation in the pig

Abstract: Objective-To compare the defibrillation eYcacy of a novel lead system placed in the middle cardiac vein with a conventional non-thoracotomy lead system. Methods-In eight pigs (weighing 35-71 kg), an electrode was advanced transvenously to the right ventricular apex (RV), with the proximal electrode in the superior caval vein (SCV). Middle cardiac vein (MCV) angiography was used to delineate the anatomy before a three electrode system (length 2 × 25 mm + 1 × 50 mm) was positioned in the vein. An active housing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…A distal shock coil far from apex may elevate DFTs [41,42], and implanting the RV lead near septum and apex may lower DFTs [43][44][45]. Adding a shock coil in the middle cardiac vein [46][47][48][49][50] or azygous vein or implanting a subcutaneous array electrode [51][52][53][54] may be a more successful strategy for low DSM patients who failed to convert ventricular fibrillation with maximum delivered energy, especially in right-sided implant patients. The extra shock coil and subcutaneous array can substantially improve the shocking vector or waveform to obtain an adequate DSM.…”
Section: Discussionmentioning
confidence: 99%
“…A distal shock coil far from apex may elevate DFTs [41,42], and implanting the RV lead near septum and apex may lower DFTs [43][44][45]. Adding a shock coil in the middle cardiac vein [46][47][48][49][50] or azygous vein or implanting a subcutaneous array electrode [51][52][53][54] may be a more successful strategy for low DSM patients who failed to convert ventricular fibrillation with maximum delivered energy, especially in right-sided implant patients. The extra shock coil and subcutaneous array can substantially improve the shocking vector or waveform to obtain an adequate DSM.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of defibrillation electrodes in the coronary sinus is not a new concept. Several animal studies have demonstrated the role of coronary sinus electrodes in lowering DFTs compared to conventional lead configurations 5,6 . Roberts et al demonstrated in pigs a 56% reduction in DFTs utilizing a shocking coil placed in the middle cardiac vein 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have demonstrated the role of coronary sinus electrodes in lowering DFTs compared to conventional lead configurations 5,6 . Roberts et al demonstrated in pigs a 56% reduction in DFTs utilizing a shocking coil placed in the middle cardiac vein 6 . Significant reduction in DFTs has also been demonstrated in humans using a temporary transvenous shocking electrode placed in a posterior or lateral coronary vein tested at the time of a standard ICD implant 7 .…”
Section: Discussionmentioning
confidence: 99%
“…These workers have, therefore, targeted this area with auxiliary shocks 19,20 . Middle cardiac vein to SVC plus active housing has a vector that includes a greater overall proportion of myocardium than RV to SVC plus active housing, 15 justifying its use in single anodal defibrillation as previously demonstrated 6 . A potential obstacle to single coil anodal middle cardiac vein defibrillation is the concern that energy delivery may be less effective than through conventional coils 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The middle cardiac vein has been demonstrated in animal 6,7 and human studies as a site with the potential to yield a low defibrillation threshold (DFT) through a lead placed transvenously. Previous investigations have compared the middle cardiac vein as a sole anode or auxiliary anode with a conventional right ventricular (RV) anodal defibrillation 6–10 . A direct comparison of defibrillation characteristics between a middle cardiac vein anode and an middle cardiac vein plus RV anode using low impedance coils and shocking to a superior vena cava (SVC) plus active housing cathode has not been undertaken.…”
Section: Introductionmentioning
confidence: 99%